Late-Onset Subretinal Silicone Oil Migration through Optic Disc Coloboma - Or Shmueli; Tareq Jaouni (Case Reports in Ophthalmology)
Introduction: This report describes a case of late onset subretinal silicone oil migration in an eye with congenital optic disc coloboma and its treatment. Case Presentation: A 15-year-old male with a history of left eye congenital optic disc coloboma and amblyopia presented with a third recurrence of retinal detachment (RD) with proliferative vitreoretinopathy. The patient underwent PPV, subretinal fluid drainage through a peripheral retinotomy, silicone oil tamponade, and endolaser around the coloboma and retinotomy. The retina re-attached successfully. However, 14 months postoperatively examination revealed high intraocular pressure (IOP) of 33 mm Hg and a sub-macular bubble of silicone oil was evident. The patient underwent sub-macular silicone oil removal. Conclusion: Here we describe the unique late-onset subretinal migration of intravitreal silicone oil following RD repair in an eye with optic disc coloboma in association with raised IOP. This case demonstrates potential mechanisms of subretinal silicone oil migration through the coloboma that serves as a passage and an increased IOP, which drives the oil from the vitreous to the subretinal space.